2021
DOI: 10.1177/03915603211046483
|View full text |Cite
|
Sign up to set email alerts
|

Outcome management of Fournier’s gangrene cases at tertiary hospital: 7 Years experience

Abstract: Objective: This study aims to describe the condition of Fournier’s gangrene in Dr. Soetomo General Hospital from January 2014 to December 2020. Material and methods: This study used a retrospective analytic design, by taking data through medical records at Dr. Soetomo General Hospital from January 2014 to December 2020. This study used total sampling with recorded data: age, gender, length of stay, outcome, location, comorbidities, causes, management, culture results, and Fournier’s gangrene severity index (FG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…We estimated that the in-hospital mortality rate of FG patients in our study population was 26.2%. In Indonesia, it has previously been identified that the mortality rate of FG ranged from 17 to 28% [ 9 , 10 ]. Ergo, our findings are in line with such previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated that the in-hospital mortality rate of FG patients in our study population was 26.2%. In Indonesia, it has previously been identified that the mortality rate of FG ranged from 17 to 28% [ 9 , 10 ]. Ergo, our findings are in line with such previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…In the latest review, the mortality in high-income countries rates between 20% and 40% (Sorensen and Krieger 2016). In developing countries, the mortality rate was between 17% and 28% [ 9 , 10 ]. Several variables have been identified as risk factors for mortality in patients with FG, including older age, congestive heart failure, renal failure, and coagulopathy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used antibiotics include metronidazole, penicillin, third-generation cephalosporins, gentamicin, carbapenems, vancomycin, fluoroquinolones, and teicoplanin. 7 , 49 52 Often, a cocktail of antibiotics is needed and microbiology advice may be necessary. Becerra et al .…”
Section: Managementmentioning
confidence: 99%
“…They also noted a high prevalence of Candida infections in their dataset 24% compared with other similar studies in other institutions (1–5%). 51 , 52 They proposed that empirical antifungals should be considered in patients with known chronic candiduria, recent intensive care unit admission, diabetes mellitus, or immunocompromised status. The antimicrobial regime is reviewed with cultures from the blood, urine, and wound debridement.…”
Section: Managementmentioning
confidence: 99%
“…Thus, this study aimed to evaluate the diagnostic performance of all scoring systems that have been proposed to predict mortality in patients with FG. To this end, we used data from Indonesia, a country with high rate of in-hospital mortality among patients with FG [ 4 , 9 ].…”
Section: Introductionmentioning
confidence: 99%